Strategi Komunikasi Interpersonal Melalui Seni Membaca Al-Qur’an Dr. Maria Ulfah dalam Meningkatkan Kemampuan Seni Baca Al-Qur’an di Indonesia - Al Mukarromah; Ingrid Kilani Johar (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2026)
Interpersonal communication is the process of sending messages between two people or a small group of people with immediate feedback. The main focus of this study is on Dr. Maria Ulfah, who played a crucial role in improving the art of Quranic recitation in Indonesia. Quranic reciters and teachers must be able to effectively implement interpersonal communication to achieve this primary goal. The purpose of this study is to discuss interpersonal communication strategies. The similarities and differences between this study and previous research are that while there are similarities, there are some differences, such as the scientific aspects discussed, the research timeframe, and the theories used to address the problem formulation. In this study, the researchers employed Miller and Steinberg's communication control theory. The research method used was descriptive qualitative research. This type of research is field research. Data sources were obtained from primary data through participant observation, structured and unstructured in-depth interviews, and documentation. Secondary data were collected from relevant literature, such as books, journals, and related literature. The sampling technique used was purposive sampling. Data analysis included data reduction, data presentation, and conclusion drawing. Data validity was then validated using triangulation of sources and methods. The results of the study indicate that Dr. Maria Ulfah's role and the process of improving the art of Quran reading in Indonesia. Specifically, Dr. Maria Ulfah's communication strategy involves the application of communication control strategies, namely logistical reasoning. Meanwhile, emotional and imbalance strategies are rarely used. She never uses sanctions because she feels they have no impact on her students. Furthermore, she utilizes both verbal and nonverbal communication in her teaching.